Sources of Demotivation among English Language Learners: Novice and Experienced Teachers’ Beliefs - Asghar Afshari; Zia Tajeddin; Gholam-Reza Abbasian (Journal of Modern Research in English Language Studies)
Motivation is a crucial factor in learning a foreign language. However, some learners may become demotivated during their experience of learning a language. Demotivation among learners has rarely been addressed from the teachers’ perspectives. The purpose of the current study was to investigate novice and experienced English as a foreign language (EFL) teachers’ perceptions of sources of demotivation among language learners. Initially, through convenience sampling, different institute teachers were contacted. Thirty novice (n = 15) and experienced (n = 15) English language teachers volunteered to participate in face-to-face semi-structured interviews to investigate their beliefs about sources of learners’ demotivation. Content analysis was run to extract relevant demotivation sources, and frequency analysis was used to summarize and report the data. The findings revealed that both novice and experienced teachers had largely similar perceptions of sources of demotivation. Both groups indicated that method of instruction, teacher personality, classmates’ behaviors, anxiety, and physical environment of the language institutes have the potential to negatively affect motivation in learners. However, they differed in the degree of importance they attached to the factors falling within each of these demotivation sources. The findings suggest that teachers need to develop an awareness of the sources of demotivation among learners and the strategies to cope with them.